2021
DOI: 10.1177/09645284211057560
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture modulates cortical excitability in a manner dependent on the parameters used

Abstract: Introduction: There is evidence that electroacupuncture (EA) acts through the modulation of brain activity, but little is known about its influence on corticospinal excitability of the primary motor cortex (M1). Objective: To investigate the influence of EA parameters on the excitability of M1 in healthy individuals. Methods: A parallel, double blind, randomized controlled trial in healthy subjects, evaluating the influence of an EA intervention on M1 excitability. Participants had a needle inserted at LI4 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They reported that the simple insertion of the needle is an adequate somatosensory stimulus to induce a significant modulation of MEP amplitude, the sign of which is specific to the investigated muscle and to the point of needle insertion. It has been demonstrated that when applying electroacupuncture or electrical stimulation to induce a motor response, it is vital that parameters creating a motor response that mimics a voluntary muscle contraction are used [81,82]. De Brito, et al [81] demonstrate that peripheral electroacupuncture or electrical stimulation that is sufficient to induce a motor contraction (30 Hz and 100 Hz) increased corticomotor responsiveness (P = 0.002), whereas stimulation at 10 Hz did not.…”
Section: Effect Of Acupuncture On the Primary Somatosensory Cortex In...mentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the simple insertion of the needle is an adequate somatosensory stimulus to induce a significant modulation of MEP amplitude, the sign of which is specific to the investigated muscle and to the point of needle insertion. It has been demonstrated that when applying electroacupuncture or electrical stimulation to induce a motor response, it is vital that parameters creating a motor response that mimics a voluntary muscle contraction are used [81,82]. De Brito, et al [81] demonstrate that peripheral electroacupuncture or electrical stimulation that is sufficient to induce a motor contraction (30 Hz and 100 Hz) increased corticomotor responsiveness (P = 0.002), whereas stimulation at 10 Hz did not.…”
Section: Effect Of Acupuncture On the Primary Somatosensory Cortex In...mentioning
confidence: 99%
“…It has been demonstrated that when applying electroacupuncture or electrical stimulation to induce a motor response, it is vital that parameters creating a motor response that mimics a voluntary muscle contraction are used [81,82]. De Brito, et al [81] demonstrate that peripheral electroacupuncture or electrical stimulation that is sufficient to induce a motor contraction (30 Hz and 100 Hz) increased corticomotor responsiveness (P = 0.002), whereas stimulation at 10 Hz did not.…”
Section: Effect Of Acupuncture On the Primary Somatosensory Cortex In...mentioning
confidence: 99%